Placenta accreta diagnosed 15 days following primary cesarean section - Krutika Parasar; Shruti Shah; Shaul Cohen; Adil Mohiuddin (Wolters Kluwer Medknow Publications, 2015)
Placenta accreta is a life-threatening obstetric complication with an ever-increasing incidence. Between 1982 and 2002, the reported incidence of placenta accreta was 1/533 pregnancies, nearly 4 times its incidence in the 1980s and 8 times its incidence in the 1970s. As Cesarean sections (C/S) become more common, so does placenta accreta, as prior C/S is a risk factor. Placenta accreta requires emergent treatment and unique anesthetic considerations. However, little research discusses the anesthetic protocol to treat this condition. This report details the anesthetic procedure used to successfully treat a patient with placenta accrete diagnosed 15 days post-C/S.